Respuesta :

Answer:

y = -x +2

Step-by-step explanation:

1. First, let's find the slope of passing through two points with the formula [tex](y_2-y_1)/(x_2-x_1)[/tex] , and use the points (0,2) and (2,0).

  • [tex](y_2-y_1)/(x_2-x_1)[/tex]
  • (0-2)/(2-0)
  • -2/2
  • -1

2. Now that we have our slope, the equation should look like this so far: y = -x + b.

3. Since b is equal to the y-intercept, we can clearly see in the given graph that the y-intercept is 2.

4. When we plug in the value of the slope and y-intercept, we now get the equation: y = -x + 2.

5. (Extra) In point-slope form, the equation is y - 2 = -x, and in standard form, it's x + y - 2 = 0.

ACCESS MORE